Nanostructured Fe-Ni Sulfide: A Multifunctional Material for Energy Generation and Storage - Zhao, Chen; Zhang, Chunyang; Bhoyate, Sanket; Kahol, Pawan K.; Kostoglou, Nikolaos; Mitterer, Christian; Hinder, Steve; Baker, Mark A.; Constantinides, Georgios; Polychronopoulou, Kyriaki; Rebholz, Claus; Gupta, Ram K. (My University, 2019)
Multifunctional materials for energy conversion and storage could act as a key solution for growing energy needs. In this study, we synthesized nanoflower-shaped iron-nickel sulfide (FeNiS) over a nickel foam (NF) substrate using a facile hydrothermal method. The FeNiS electrode showed a high catalytic performance with a low overpotential value of 246 mV for the oxygen evolution reaction (OER) to achieve a current density of 10 mA/cm2, while it required 208 mV at 10 mA/cm2 for the hydrogen evolution reaction (HER). The synthesized electrode exhibited a durable performance of up to 2000 cycles in stability and bending tests. The electrolyzer showed a lower cell potential requirement for a FeNiS-Pt/C system (1.54 V) compared to a standard benchmark IrO2-Pt/C system (1.56 V) to achieve a current density of 10 mA/cm2. Furthermore, the FeNiS electrode demonstrated promising charge storage capabilities with a high areal capacitance of 13.2 F/cm2. Our results suggest that FeNiS could be used for multifunctional energy applications such as energy generation (OER and HER) and storage (supercapacitor).
Keywords: FeNiS; electrocatalyst; cyclic voltammetry; supercapacitor; cyclic stability; flexibility